Kadar Krioprotektan Gliserol dan Dimethylsulfoxide Terbaik pada Pengencer Astaxanthin Fosfat Kuning Telur Bebek Terhadap Kualitas Semen Beku Babi - Bebas, Wayan; Gorda, Wayan (Jurnal Veteriner; Vol 21 No 1 (2020), 2020)
The aim of this study to examine the addition of cryoprotectant glycerol and dimethylsulfoxide (DMSO) in  astaxanthin phosphate duck egg yolk on the quality of frozen boar semen. Each of the cryoprotectants distinguished its concentration ie : 4%, 6%, 8%, 10%, and 12% for freezing of semen. Semen was collected from one Landrace boar then  performed macroscopically and microscopically. Semen was  divided into 10 tubes each diluted with the duck egg yolk astaxanthin phosphate extender diluent then stored at 20oC for 2 hours, centrifugation for 15 minutes (2000 rpm) then taken the pellet with 1 ml of supernatant. The pellets were diluted with astaxanthin phosphate duck egg yolk extender containing various concentration (4, 6, 8, 10, and 12%). Semen was packed with 0.5 mL straw and performed equilibration for 2 hours (4oC). do aeration above liquid N2 vapor for 10 minutes, then dipped in liquid N2. Semen was stored in liquid nitrogen container for 24 hours , and then quality of spermatozoa was evaluated post thawing. The results of the study showed that addition of cryoprotectan glycerol and DMSO were no difference significant (p>0,05) on the quality of frozen semen, but cryoprotectant concentrations (4%, 6%, 8%, 10%, and 12%) significantly affected (p <0.05) the quality of frozen semen. Glycerol with a concentration of 4% produces the best quality frozen semen, whereas DMSO with a concentration of 6% produces the best quality frozen semen.